Temperature optima of a natural diatom population increases as global warming proceeds - Hattich, Giannina S. I. (Springer Nature, 2025)
Studies in laboratory-based experimental evolution have demonstrated that phytoplankton species can rapidly adapt to higher temperatures. However, adaptation processes and their pace remain largely unknown under natural conditions. Here, by comparing resurrected Skeletonema marinoi strains from the Baltic Sea during the past 60 years, we show that modern S. marinoi have increased their temperature optima by 1 degrees C. With the increasing ability to grow in higher temperatures, growth rates in cold water decreased. Modern S. marinoi modified their valve:girdle ratio under warmer temperatures, which probably increases nutrient uptake ability. This was supported by the upregulation of several genes related to nitrate metabolism in modern strains grown under high temperatures. Our approach using resurrected strains demonstrates the adaptation potential of naturally occurring marine diatoms to increasing temperatures as global warming proceeds and exemplifies a realistic pace of evolution, which is an order of magnitude slower than estimated by experimental evolution.